2020
DOI: 10.1038/s41598-020-59184-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Agronomic Traits and Grain Iron and Zinc Concentrations in a Doubled Haploid Population of Rice (Oryza sativa L.)

Abstract: The development of micronutrient dense rice varieties with good agronomic traits is one of the sustainable and cost-effective approaches for reducing malnutrition. Identification of QTLs for high grain Fe and Zn, yield and yield components helps in precise and faster development of high Fe and Zn rice. We carried out a three-season evaluation using IR05F102 x IR69428 derived doubledhaploid population at IRRI. Inclusive composite interval mapping was carried out using SNP markers and Best Linear Unbiased Estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 63 publications
4
40
0
Order By: Relevance
“…On CaLG05, QTLs CaqFe 5.1- CaqZn 5.1 were colocalized within the SNP marker interval of SCA5_37174786-SCA5_35312501. Previous studies have reported QTL colocalization for micronutrient concentration in chickpea on chromosomes 4, 5, and 7 ( 2 ) and also in rice ( 10 ). Hence, these genomic regions on chromosome 4 may contain conserved QTLs for seed Fe and Zn concentrations across diverse genetic backgrounds.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On CaLG05, QTLs CaqFe 5.1- CaqZn 5.1 were colocalized within the SNP marker interval of SCA5_37174786-SCA5_35312501. Previous studies have reported QTL colocalization for micronutrient concentration in chickpea on chromosomes 4, 5, and 7 ( 2 ) and also in rice ( 10 ). Hence, these genomic regions on chromosome 4 may contain conserved QTLs for seed Fe and Zn concentrations across diverse genetic backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…Pleiotropy or tight linkage of genes controlling multiple traits may be the reason for the colocalization of QTLs ( 50 ). These regions with colocated QTLs will be useful for simultaneous improvement using marker-assisted selection ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Crops are subjected to genotype by environment interaction (GxE) and to agronomic management practices. Environmental factors such as soil redox potential, pH, soil structure and texture, organic matter content and climate conditions, among others, influence GxE interaction and may affect rice zinc levels accumulation [102,103]. This is a consequence of the alteration of quantitative trait locus (QTL) responsible for the absorption and translocation of zinc to the grain in biofortified varieties [68].…”
Section: Plos Onementioning
confidence: 99%
“…Such non-segregating populations include doubled haploid lines (DHLs), near isogenic lines (NILs), recombinant inbred lines (RILs), chromosomal segment substitution lines (CSSLs). Among them the DHLs can be a very useful resource for identi cation of yield QTLs and heterosis associated loci [8,9,10,11,12], in the context of hybrid rice improvement. Development of the above mentioned immortal and xed populations from popular high-yielding rice hybrids could be a valuable resource for mapping various agronomically important traits relevant to hybrid rice [13,14].…”
Section: Introductionmentioning
confidence: 99%